«Donne io vel dico da parte de Orlando ». Notes on women reading the chivalric poem in the 16th century (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
In the proem of canto eighteen of Hercole, Giovan Battista Giraldi Cinzio addresses the «donne gentili». The octaves that follow recount a «lascivo amore, e fiamme scelerate»; but the intent, the author warns, is not to tarnish the faith of the aforementioned, defined shortly afterwards as inviolable, but rather to define a vice not to be followed. The narrative is intended to serve as an exemplum and the proem is elected as a form of dialogue. Cinzio’s is not the only case within the sixteenth-century chivalric production in which the author, through allocutionary formulas, addresses his readers. In fact, he is accompanied by a series of texts that follow in the wake of the cantari, Boiardo, and Ludovico Ariosto’s Furioso: from Cassio da Narni’s La morte del Danese to Vincenzo Brusantini’s Angelica innamorata, up to the more famous Amadigi by Bernardo Tasso. Each of them establishes a dialogue with the female audience, whether noble or indefinite, no longer exclusively dedicated to working with «l’ago e ’l panno».
Keywords: Women; exemplum; Giraldi Cinzio; Ariosto; Cassio da Narni; Brusantini; Chivalric Novel